Biomass-derived silicon-carbon negative electrode material and preparation method and application thereof
The silicon carbon negative electrode material is prepared by collaborative composite of biomass-derived carbon and diatom biosilicon dioxide, which solves the problem of degradation of thermal stability and chemical stability of the negative electrode material of lithium-ion batteries, and achieves the improvement of high energy density and cyclic stability.
Patent Information
- Application Number
- CN202411526641.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-30
Smart Images

Figure CN119430129A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a biomass-derived silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid growth of the new energy vehicle market and the continuous development of energy storage technology, the market demand for silicon-carbon negative electrode materials has also shown a rapid growth trend. Silicon-carbon negative electrode materials can significantly improve the energy density and range of batteries, and are one of the key materials in the fields of new energy vehicles, energy storage systems, etc. In actual application, silicon-carbon negative electrode materials face technical challenges such as volume expansion, low initial efficiency, and high cost. Volume expansion may lead to problems such as decreased thermal and chemical stability, rapid capacity decay, and deterioration of cycle performance. Low initial efficiency means that the energy utilization rate of the battery is low during the first charge and discharge process. In terms of cost, the production cost of silicon-carbon negative electrode materials is relatively high, which increases the overall cost of the battery.
[0003] Silicon-carbon negative electrode material is considered to be the most promising negative electrode material for the new generation of high-energy-density lithium-ion batteries because its theoretical energy density is much higher than that of graphite (372mAh / g). Summary of the invention
[0004] The present invention aims to solve the technical problems of decreased thermal stability and chemical stability, rapid capacity decay and deteriorated cycle performance of negative electrode materials of lithium-ion batteries during application. The present invention provides a biomass-derived silicon-carbon negative electrode material synergistically composited with a biomass derivative and diatom biosilica, and a preparation method and application thereof, which utilizes the enhancement effect of the specific capacity of biomass-derived carbon and the porous characteristics of diatoms to synergistically improve the specific capacity and stability of lithium-ion batteries.
[0005] The inventive concept of the present invention is as follows: the present invention uses rice and diatom as raw materials, and the rice is subjected to acid washing, alkali extraction, reprecipitation, drying, carbonization and ball milling to obtain biomass-derived carbon; the diatom is subjected to oxidative acid hydrolysis, filtration washing, drying and calcination to obtain diatom biosilica; and then the biomass-derived carbon and diatom biosilica are synergistically compounded to obtain silicon-carbon negative electrode material. The biomass-derived silicon-carbon material combines the high capacity of silicon-based active materials and the good conductivity of carbon-based conductive materials, and can provide higher theoretical capacity and actual capacity, thereby significantly improving the energy density of the battery; at the same time, the biomass-derived silicon-carbon material has a porous nanostructure and morphology, which is conducive to alleviating the volume expansion of silicon during the lithium insertion process, thereby improving the structural stability of the material. Therefore, the silicon-carbon negative electrode material of the present invention has the characteristics of high porosity and large specific surface area, which can effectively reduce the volume expansion of the negative electrode material during the battery charging and discharging process, maintain the stability of the electrode structure, and has the advantages of high specific capacity, excellent initial coulomb efficiency and good safety performance. It is applied to lithium-ion batteries and can effectively improve the battery's charge and discharge capacity and cycle stability.
[0006] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a negative electrode material, comprising the following steps:
[0007] Preparation of biomass-derived carbon:
[0008] (1) adding rice husk powder to an acid solution for pickling, and extracting sediment by vacuum filtration;
[0009] (2) adding an alkaline solution to the sediment extracted in step (1) for alkaline extraction, boiling under reflux, and vacuum filtering again to extract the solution;
[0010] (3) adding deionized water and ethanol to the solution extracted in step (2), then dropping sulfuric acid, adding polyethylene glycol under stirring, adjusting the pH value to acidic, allowing to stand, and filtering to obtain a precipitate;
[0011] (4) washing the precipitate obtained in step (3) to neutrality, drying, carbonizing and grinding to obtain the biomass-derived carbon;
[0012] Preparation of diatom biogenic silica:
[0013] 1) Mix hydrogen peroxide, hydrochloric acid and diatom, perform oxidative acid hydrolysis, and let stand to obtain a white precipitate;
[0014] 2) washing, centrifuging or filtering, vacuum drying and calcining the white precipitate to obtain the diatom biogenic silica;
[0015] The biomass-derived carbon is mixed with the diatom biosilica to obtain the negative electrode material.
[0016] Preferably, in step (1), the rice husk powder is obtained by washing and crushing rice husks.
[0017] Preferably, in step (1), the acid solution is hydrochloric acid, and the concentration of the hydrochloric acid is 0.5-2 mol / L.
[0018] Preferably, in step (2), the alkaline solution is NaOH or KOH, and the mass fraction of the alkaline solution is 5-15%.
[0019] Preferably, in step (2), the reflux boiling time is 4-8 hours.
[0020] Preferably, in step (3), the volume ratio of the extracted solution, deionized water and ethanol is (1-3): (1-3): 1.
[0021] Preferably, in step (3), the concentration of sulfuric acid is 0.5-2 mol / L.
[0022] Preferably, in step (3), the mass ratio of polyethylene glycol to rice husk powder is (8-10):1.
[0023] Preferably, in step (3), the pH value is 2-4.
[0024] Preferably, in step (3), the standing time is 12-24 hours.
[0025] Preferably, in step (4), the drying temperature is 80-120°C.
[0026] Preferably, in step (4), the carbonization is a heat treatment at 1000-1600° C. for 2-6 hours under an inert atmosphere, and the inert atmosphere is an argon atmosphere or a nitrogen atmosphere.
[0027] Preferably, in step (4), the grinding is performed by ball milling at a rotation speed of 500-700 rpm for 8-24 hours.
[0028] Preferably, in step 1), the diatom is collected by precipitation according to the precipitation characteristics of Nitzschia palea.
[0029] Preferably, in step 1), the mass fraction of hydrogen peroxide is 25-35%.
[0030] Preferably, in step 1), the concentration of the hydrochloric acid is 1-2 mol / L.
[0031] Preferably, in step 1), the volume ratio of hydrogen peroxide to hydrochloric acid is (0.8-1.5):1.
[0032] Preferably, in step 1), the standing time is 24-48 hours to remove organic matter in the diatom cells until a white precipitate is obtained.
[0033] Preferably, in step 2), the cleaning is performed with deionized water for 2-4 times.
[0034] Preferably, in step 2), the vacuum drying temperature is 60-80° C., and the drying time is 16-24 hours.
[0035] Preferably, in step 2), the filtration is performed by filtering with sieve silk to collect diatom biogenic silica.
[0036] Preferably, in step 2), the calcination is a heat treatment at 550-700° C. for 2-6 hours under an inert atmosphere, and the inert atmosphere is an argon atmosphere or a nitrogen atmosphere.
[0037] Preferably, the mass ratio of the biomass-derived carbon to the diatom biogenic silica is (0.1-0.8):1.
[0038] Preferably, the biomass-derived carbon and diatom biogenic silica are mixed by ball milling, the rotation speed of the ball mill is 500-700 rpm, and the ball milling time is 8-24 hours.
[0039] The second aspect of the present invention provides a negative electrode material, which is prepared by the above-mentioned method for preparing the negative electrode material, and the specific surface area of the negative electrode material is 25-30m 2 The negative electrode material of the present invention utilizes the enhancement effect of the comparative capacity of biomass-derived carbon and the porous characteristics of diatoms, and the synergistic combination of the two realizes the enhancement of the comparative capacity.
[0040] A third aspect of the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the negative electrode material described above.
[0041] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0042] (1) The present invention uses rice and diatoms as raw materials, and synthesizes the biomass-derived carbon obtained by acid washing, alkali extraction, reprecipitation, drying, carbonization and ball milling of rice with diatom biosilica obtained by precipitation collection, oxidative acid hydrolysis, filtration washing, drying and calcination of diatoms to prepare a silicon-carbon negative electrode material. The silicon-carbon negative electrode material has the characteristics of high porosity and large specific surface area, can effectively reduce the volume expansion of the negative electrode material during the battery charging and discharging process, maintain the stability of the electrode structure, and is applied to lithium-ion batteries, which is beneficial to improving the battery's charge and discharge capacity and cycle stability.
[0043] (2) The negative electrode material of the present invention has abundant raw material sources and low cost, which can greatly reduce the cost of raw materials and effectively reduce environmental impact, thus promoting its commercial application. The silicon-carbon negative electrode material prepared by combining diatom biosilica with high porosity and large specific surface area with biomass-derived carbon is applied to lithium-ion batteries, and the initial discharge specific capacity can reach 2100 mAh / g. The capacity retention rate after 50 cycles at a current density of 103 mA / g is high, which can be no less than 95%, and can even reach 95.23%. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a SEM image of the diatom biogenic silica prepared in Example 1;
[0045] Figure 2 XRD pattern of the negative electrode material prepared in Example 2;
[0046] Figure 3 The cycle performance diagram of a lithium-ion battery (current density of 100 mA / g) assembled with the negative electrode material prepared in Example 1;
[0047] Figure 4 The charge and discharge curves of the battery assembled with the negative electrode materials prepared in Comparative Example 1 and Comparative Example 2;
[0048] Figure 5 The figure is a cycle performance diagram of a battery (current density is 100 mA / g) assembled with the negative electrode materials prepared in Comparative Example 1 and Comparative Example 2;
[0049] Figure 6 The graph is a cycle performance graph of a battery (current density is 150 mA / g) assembled with the negative electrode materials prepared in Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0050] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0051] Example 1
[0052] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0053] (1) Preparation of biomass-derived carbon (RHs-1100)
[0054] 100g rice husk was washed with deionized water, crushed and immersed in 500mL of 2mol / L HCl. The sediment was extracted by vacuum filtration and added to 500mL of 15% NaOH solution, and then the mixture was refluxed and boiled for 8 hours. The extraction solution was then extracted by vacuum filtration, and deionized water and ethanol were added (the volume ratio of extraction solution, deionized water and ethanol was 3:1:1). Subsequently, 2mol / L H2SO4 was continuously dripped into the extraction solution, and 10g PEG-2000 was added under magnetic stirring. Precipitation began to appear until pH = 3. The mixture was allowed to stand for 30 minutes and then filtered. The filtrate precipitate was washed with deionized water until it was neutral. After drying at 100℃ overnight, it was placed in a tube furnace and calcined at 1100℃ for 4 hours at a heating rate of 5℃ / min under Ar atmosphere. The carbonized product was collected and ball milled at a speed of 500rpm for 12 hours to obtain the desired biomass-derived carbon material, which was recorded as RHs-1100.
[0055] (2) Preparation of diatom biogenic silica
[0056] According to the precipitation characteristics of Nitzschia palea, diatoms were collected by precipitation. The diatoms were added to a mixed solution of H2O2 and HCl (30% H2O2 and 2mol / L HCl in a volume ratio of 1:1), left to stand for 48 hours, then filtered with a sieve, and the precipitate was washed three times with deionized water. It was vacuum dried at 80°C for 24 hours, then placed in a tubular furnace, heated to 650°C at a heating rate of 5°C / min in an Ar atmosphere, and calcined for 4 hours. After carbonization, diatom biosilica was obtained.
[0057] (3) Preparation of silicon-carbon negative electrode materials
[0058] The RHs-1100 prepared in step (1) and the diatom biosilica prepared in step (2) were mixed in a mass ratio of 1:7, and ball-milled at a rotation speed of 500 rpm for 1 hour to obtain the silicon-carbon negative electrode material of this embodiment.
[0059] Example 2
[0060] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0061] (1) Preparation of biomass-derived carbon (RHs-1050)
[0062] 100 g of rice husk was washed with deionized water, crushed and immersed in 500 mL of 1.5 mol / L HCl. The sediment was extracted by vacuum filtration and added to 500 mL of 15% NaOH solution, and then the mixture was refluxed and boiled for 7 hours. The solution was extracted by vacuum filtration again, and deionized water and ethanol were added (the volume ratio of extraction solution, deionized water and ethanol was 3:1:1). Subsequently, 1.5 mol / L H2SO4 was continuously dripped into the extraction solution, and 10 g PEG-2000 was added under magnetic stirring. Precipitation began to appear until pH = 3. The mixture was allowed to stand for 30 minutes, then filtered, and the filtrate precipitate was washed with deionized water until it was neutral. After drying at 100°C overnight, it was placed in a tubular furnace and calcined at 1050°C for 4 hours at a heating rate of 5°C / min under Ar atmosphere. The carbonized product was collected and ball-milled at 500 rpm for 12 hours to obtain the desired biomass-derived carbon material, which was recorded as RHs-1050.
[0063] (2) Preparation of diatom biogenic silica
[0064] According to the precipitation characteristics of Nitzschia palea, diatoms were collected by precipitation. The diatoms were added to a mixed solution of H2O2 and HCl (30% H2O2 and 2mol / L HCl in a volume ratio of 1:1), left to stand for 36 hours, then filtered with a sieve, and the precipitate was washed three times with deionized water. It was vacuum dried at 80°C for 24 hours, then placed in a tubular furnace, heated to 600°C at a heating rate of 5°C / min in an Ar atmosphere, and calcined for 4 hours. Diatom biosilica was obtained after carbonization.
[0065] (3) Preparation of silicon-carbon negative electrode materials
[0066] The RHs-1050 prepared in step (1) and the diatom biosilica prepared in step (2) were mixed in a mass ratio of 1:7, and ball-milled at a rotation speed of 500 rpm for 1 hour to obtain the silicon-carbon negative electrode material of this embodiment.
[0067] Example 3
[0068] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0069] (1) Preparation of biomass-derived carbon (RHs-1000)
[0070] 100g rice husk was washed with deionized water, crushed and immersed in 500mL of 0.5mol / L HCl. The sediment was extracted by vacuum filtration and added to 500mL of 15% NaOH solution, and then the mixture was refluxed and boiled for 6 hours. The extraction solution was then extracted by vacuum filtration, and deionized water and ethanol were added (the volume ratio of the extraction solution, deionized water and ethanol was 3:1:1). Subsequently, 1mol / L H2SO4 was continuously dripped into the extraction solution, and 10g PEG-2000 was added under magnetic stirring. Precipitation began to appear until pH = 3. The mixture was allowed to stand for 30 minutes and then filtered. The filtrate precipitate was washed with deionized water until it was neutral. After drying at 100℃ overnight, it was placed in a tube furnace and calcined at 1000℃ for 4 hours at a heating rate of 5℃ / min under Ar atmosphere. The carbonized product was collected and ball milled at a speed of 500rpm for 12 hours to obtain the desired biomass-derived carbon material, which was recorded as RHs-1000.
[0071] (2) Preparation of diatom biogenic silica
[0072] According to the precipitation characteristics of Nitzschia palea, diatoms were collected by precipitation. The diatoms were added to a mixed solution of H2O2 and HCl (30% H2O2 and 2mol / L HCl in a volume ratio of 1:1), left to stand for 48 hours, then filtered with a sieve, and the precipitate was washed three times with deionized water. It was vacuum dried at 80°C for 24 hours, then placed in a tubular furnace, heated to 600°C at a heating rate of 3°C / min in an Ar atmosphere, and calcined for 4 hours. Diatom biosilica was obtained after carbonization.
[0073] (3) Preparation of silicon-carbon negative electrode materials
[0074] The RHs-1000 prepared in step (1) and the diatom biosilica prepared in step (2) were mixed in a mass ratio of 1:7, and ball-milled at a speed of 500 rpm for 1 hour to obtain the silicon-carbon negative electrode material of this embodiment.
[0075] Example 4
[0076] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0077] (1) Preparation of biomass-derived carbon (RHs-950)
[0078] 100g rice husk was washed with deionized water, crushed and immersed in 500mL of 0.5mol / L HCl. The sediment was extracted by vacuum filtration and added to 500mL of 15% NaOH solution, and then the mixture was refluxed and boiled for 6 hours. The extraction solution was then extracted by vacuum filtration, and deionized water and ethanol were added (the volume ratio of extraction solution, deionized water and ethanol was 3:1:1). Subsequently, 0.5mol / L H2SO4 was continuously dripped into the extraction solution, and 10g PEG-2000 was added under magnetic stirring. Precipitation began to appear until pH = 3. The mixture was allowed to stand for 30 minutes and then filtered. The filtrate precipitate was washed with deionized water until it was neutral. After drying at 100℃ overnight, it was placed in a tube furnace and heated to 950℃ at a heating rate of 5℃ / min under Ar atmosphere for 4 hours. The carbonized product was collected and ball milled at a speed of 500rpm for 12 hours to obtain the desired biomass-derived carbon material, which was recorded as RHs-950.
[0079] (2) Preparation of diatom biogenic silica
[0080] According to the precipitation characteristics of Nitzschia palea, diatoms were collected by precipitation. The diatoms were added to a mixed solution of H2O2 and HCl (30% H2O2 and 2mol / L HCl in a volume ratio of 1:1), left to stand for 48 hours, then filtered with a sieve, and the precipitate was washed three times with deionized water. It was vacuum dried at 80°C for 24 hours, then placed in a tubular furnace, heated to 550°C at a heating rate of 4°C / min in an Ar atmosphere, and calcined for 4 hours. Diatom biosilica was obtained after carbonization.
[0081] (3) Preparation of silicon-carbon negative electrode materials
[0082] The RHs-950 prepared in step (1) and the diatom biosilica prepared in step (2) were mixed in a mass ratio of 1:7, and ball-milled at a speed of 500 rpm for 1 hour to obtain the silicon-carbon negative electrode material of this embodiment.
[0083] Example 5
[0084] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0085] (1) Preparation of biomass-derived carbon (RHs-900)
[0086] 100 g of rice husk was washed with deionized water, crushed and immersed in 500 mL of 1 mol / L HCl. The sediment was extracted by vacuum filtration and added to 500 mL of 15% NaOH solution, and then the mixture was refluxed and boiled for 8 hours. The extraction solution was then extracted by vacuum filtration, and deionized water and ethanol were added (the volume ratio of the extraction solution, deionized water and ethanol was 3:1:1). Subsequently, 1 mol / L H2SO4 was continuously dripped into the extraction solution, and 10 g PEG-2000 was added under magnetic stirring. Precipitation began to appear until pH = 3. The mixture was allowed to stand for 30 minutes and then filtered. The filtrate precipitate was washed with deionized water until it was neutral. After drying at 100 ° C overnight, it was placed in a tube furnace and heated to 900 ° C at a heating rate of 5 ° C / min under Ar atmosphere for 6 hours. The carbonized product was collected and ball milled at a speed of 500 rpm for 12 hours to obtain the desired biomass-derived carbon material, which was recorded as RHs-900.
[0087] (2) Preparation of diatom biogenic silica
[0088] According to the precipitation characteristics of Nitzschia palea, diatoms were collected by precipitation. The diatoms were added to a mixed solution of H2O2 and HCl (30% H2O2 and 2mol / L HCl in a volume ratio of 1:1), left to stand for 48 hours, then filtered with a sieve, and the precipitate was washed three times with deionized water. It was vacuum dried at 80°C for 24 hours, then placed in a tubular furnace, heated to 500°C at a heating rate of 4°C / min in an Ar atmosphere, and calcined for 4 hours. Diatom biosilica was obtained after carbonization.
[0089] (3) Preparation of silicon-carbon negative electrode materials
[0090] The RHs-900 prepared in step (1) and the diatom biosilica prepared in step (2) were mixed in a mass ratio of 1:7, and ball-milled at a speed of 500 rpm for 1 hour to obtain the silicon-carbon negative electrode material of this embodiment.
[0091] Example 6
[0092] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0093] (1) Preparation of biomass-derived carbon (RHs-800)
[0094] 100g rice husk was washed with deionized water, crushed and immersed in 500mL of 2mol / L HCl. The sediment was extracted by vacuum filtration and added to 500mL of 15% NaOH solution, and then the mixture was refluxed and boiled for 8 hours. The extraction solution was then extracted by vacuum filtration, and deionized water and ethanol were added (the volume ratio of extraction solution, deionized water and ethanol was 3:1:1). Subsequently, 2mol / L H2SO4 was continuously dripped into the extraction solution, and 12g PEG-2000 was added under magnetic stirring. Precipitation began to appear until pH = 3. The mixture was allowed to stand for 30 minutes and then filtered. The filtrate precipitate was washed with deionized water until it was neutral. After drying at 100℃ overnight, it was placed in a tube furnace and calcined at 800℃ for 6 hours at a heating rate of 5℃ / min under Ar atmosphere. The carbonized product was collected and ball milled at a speed of 500rpm for 12 hours to obtain the desired biomass-derived carbon material, which was recorded as RHs-800.
[0095] (2) Preparation of diatom biogenic silica
[0096] According to the precipitation characteristics of Nitzschia palea, diatoms were collected by precipitation. The diatoms were added to a mixed solution of H2O2 and HCl (30% H2O2 and 2mol / L HCl in a volume ratio of 1:1), left to stand for 48 hours, then filtered with a sieve, and the precipitate was washed three times with deionized water. It was vacuum dried at 80°C for 24 hours, then placed in a tubular furnace, heated to 650°C at a heating rate of 5°C / min in an Ar atmosphere, and calcined for 4 hours. After carbonization, diatom biosilica was obtained.
[0097] (3) Preparation of silicon-carbon negative electrode materials
[0098] The RHs-800 prepared in step (1) and the diatom biosilica prepared in step (2) were mixed in a mass ratio of 1:7, and ball-milled at a speed of 500 rpm for 1 hour to obtain the silicon-carbon negative electrode material of this embodiment.
[0099] Comparative Example 1
[0100] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0101] (1) Preparation of biomass-derived carbon (RHs-1100)
[0102] 100g rice husk was washed with deionized water, crushed and immersed in 500mL of 2mol / L HCl. The sediment was extracted by vacuum filtration and added to 500mL of 15% NaOH solution, and then the mixture was refluxed and boiled for 8 hours. The extraction solution was then extracted by vacuum filtration, and deionized water and ethanol were added (the volume ratio of extraction solution, deionized water and ethanol was 3:1:1). Subsequently, 2mol / L H2SO4 was continuously dripped into the extraction solution, and 10g PEG-2000 was added under magnetic stirring. Precipitation began to appear until pH = 3. The mixture was allowed to stand for 30 minutes and then filtered. The filtrate precipitate was washed with deionized water until it was neutral. After drying at 100℃ overnight, it was placed in a tube furnace and calcined at 1100℃ for 4 hours at a heating rate of 5℃ / min under Ar atmosphere. The carbonized product was collected and ball milled at a speed of 500rpm for 12 hours to obtain the desired biomass-derived carbon material, which was recorded as RHs-1100.
[0103] (2) Preparation of silicon-carbon negative electrode materials
[0104] The RHs-1100 prepared in step (1) was mixed with Si particles in a mass ratio of 5:2, and ball-milled at a rotation speed of 500 rpm for 1 hour to obtain the silicon-carbon negative electrode material of this comparative example.
[0105] Comparative Example 2
[0106] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0107] Graphite and Si particles were mixed in a mass ratio of 5:2, and ball-milled at a rotation speed of 500 rpm for 1 hour to obtain the silicon-carbon negative electrode material of this comparative example.
[0108] Performance Testing
[0109] 1. Physical phase and morphology
[0110] Figure 1 This is a SEM image of the diatom biogenic silica prepared in Example 1. Figure 1 It can be seen that diatom biogenic silica has an orderly distributed 3D, hierarchical porous structure.
[0111] Figure 2 The XRD diagram of the negative electrode material prepared in Example 2, wherein the horizontal axis 2Theta represents the 2θ diffraction angle, and the vertical axis Intensity represents the intensity of the diffraction peak. Figure 2 It can be seen that the RHs-1050 sample has sharp diffraction peaks at 2θ=21.6° and 26.5°, corresponding to the (100) and (101) planes of SiO2, respectively.
[0112] 2. Specific surface area and electrochemical performance
[0113] The specific surface areas of the negative electrode materials prepared in Examples 1-6 and Comparative Examples 1-2 were measured using a TriStar II 3020 / 3-Flex Micromeritics America instrument. The results are shown in Table 1.
[0114] The negative electrode materials, carbon black and polyacrylic acid prepared in Example 1 and Comparative Examples 1-2 were mixed and dispersed in deionized water in a mass ratio of 8:1:1. The obtained slurry was coated on copper foil with a coating thickness of 20 μm to obtain an electrode sheet; the electrode sheet was then dried in a vacuum oven at 80°C for 12 hours. The electrode sheet was cut into discs with a diameter of 16 mm and used for battery assembly. The loading amount of active material was 0.1 mg. The electrolyte was 1.2 mol / L LiPF6, EC / EMC (volume ratio of 1:3), 15 wt% FEC and 3 wt% VC. Lithium foil was used as the counter electrode and reference electrode, and Celgard 2400 was used as the separator. Finally, the assembly of the CR2016 button cell was completed in a glove box filled with Ar.
[0115] Test conditions: The button cells prepared in Examples 1-6 and Comparative Examples 1-2 were heated at 25°C, with a current density of 100-150 mA / g and a voltage range of 0.01-3 V (relative to Li / Li + ) under the condition of constant current charge and discharge cycle test, the results are shown in Table 1 and Figure 3-6 shown.
[0116] Table 1:
[0117] First charge and discharge capacity (mAh / g) Initial coulombic efficiency (%) <![CDATA[Specific surface area (m 2 / g)]]> Example 1 2093.1 101.2 28.62 Example 2 2007.6 97.5 28.44 Example 3 1879.2 91.7 27.66 Example 4 1790.1 89.5 26.83 Example 5 1773.4 86.8 26.51 Example 6 1675.9 84.1 25.62 Comparative Example 1 1182.7 96.7 12.93 Comparative Example 2 1384.8 97.4 13.54
[0118] From Table 1 and Figure 3-6 It can be seen that the first discharge capacity (Specific capacity) and specific surface area of the battery assembled by the negative electrode materials of Examples 1-6 of the present invention are significantly better than those of Comparative Examples 1-2. The initial coulombic efficiency (Coulombi c effiency) of Examples 1-2 is better than that of Comparative Examples 1-2. The reason may be that the silicon-carbon material prepared by the present invention uses the synergistic composite effect of biomass-derived carbon and diatom biosilica as the negative electrode material of the lithium battery, and its high porosity and high specific surface area improve the conductivity, charge and discharge capacity and initial coulombic efficiency of the material. The reason why the initial coulombic efficiency of Examples 3-6 is lower than that of Comparative Examples 1-2 may be attributed to the high specific surface area of the prepared negative electrode materials; during the initial discharge process, the electrolyte reacts with the surface of the negative electrode material, consuming Li + , which is caused by the formation of solid electrolyte interface film (SEI).
[0119] Figure 5The cycle performance diagram of the battery assembled with the negative electrode materials prepared in Comparative Example 1 (Biomass / Si) and Comparative Example 2 (Graphite / Si) under constant current charge and discharge conditions in the voltage range of 0.01-3V and the current density of 100mA / g. After 25 cycles, the discharge capacity is maintained at about 1390mAh / g and 1090mAh / g, respectively.
[0120] Figure 6 The cycle performance diagram of the battery assembled with the negative electrode materials prepared in Comparative Example 1 (Biomass / Si) and Comparative Example 2 (Graphite / Si) under constant current charge and discharge conditions in the voltage range of 0.01-3V and the current density of 150mA / g. In 40-50 cycles, the discharge capacity is maintained at about 1225mAh / g and 1030mAh / g, respectively.
[0121] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode material, characterized in that: The following steps are involved: Preparation of biomass-derived carbon: (1) adding rice husk powder to an acid solution for pickling, and extracting sediment by vacuum filtration; (2) adding an alkaline solution to the sediment extracted in step (1) for alkaline extraction, boiling under reflux, and vacuum filtering again to extract the solution; (3) adding deionized water and ethanol to the solution extracted in step (2), then dropping sulfuric acid, adding polyethylene glycol under stirring, adjusting the pH value to acidic, allowing to stand, and filtering to obtain a precipitate; (4) washing the precipitate obtained in step (3) to neutrality, drying, carbonizing and grinding to obtain the biomass-derived carbon; Preparation of diatom biogenic silica: 1) Mix hydrogen peroxide, hydrochloric acid and diatom, perform oxidative acid hydrolysis, and let stand to obtain a white precipitate; 2) washing, centrifuging or filtering, vacuum drying and calcining the white precipitate to obtain the diatom biogenic silica; The biomass-derived carbon is mixed with the diatom biosilica to obtain the negative electrode material.
2. The method for preparing the negative electrode material according to claim 1, characterized in that: In step (1), the acid solution is hydrochloric acid, and the concentration of the hydrochloric acid is 0.5-2 mol / L.
3. The method for preparing the negative electrode material according to claim 1, characterized in that: In step (2), the alkaline solution is NaOH or KOH, and the mass fraction of the alkaline solution is 5-15%; and / or the reflux boiling time is 4-8 hours.
4. The method for preparing the negative electrode material according to claim 1, characterized in that: In step (3), the volume ratio of the extracted solution, deionized water and ethanol is (1-3): (1-3): 1; and / or the concentration of the sulfuric acid is 0.5-2 mol / L; and / or the mass ratio of the polyethylene glycol to the rice husk powder is (8-10): 1; and / or the pH value is 2-4.
5. The method for preparing the negative electrode material according to claim 1, characterized in that: In step (4), the drying temperature is 80-120°C; and / or the carbonization is heat treatment at 1000-1600°C for 2-6 hours under an inert atmosphere; and the grinding is ball milling at a rotation speed of 500-700 rpm for 8-24 hours.
6. The method for preparing the negative electrode material according to claim 1, characterized in that: In step 1), the mass fraction of the hydrogen peroxide is 25-35%; and / or the concentration of the hydrochloric acid is 1-2 mol / L; and / or the volume ratio of the hydrogen peroxide to the hydrochloric acid is (0.8-1.5):
1.
7. The method for preparing the negative electrode material according to claim 1, characterized in that: In step 2), the vacuum drying temperature is 60-80° C.; and / or, the calcination is a heat treatment at 550-700° C. for 2-6 hours under an inert atmosphere.
8. The method for preparing the negative electrode material according to claim 1, characterized in that: The mass ratio of the biomass-derived carbon to the diatom biogenic silica is (0.1-0.8):
1.
9. A negative electrode material, characterized in that: The method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 8 has a specific surface area of 25 to 30 m 2 / g.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the negative electrode material according to claim 9.
Citation Information
Patent Citations
Diatomite-derived silicon-carbon negative electrode material, preparation method thereof and application of diatomite-derived silicon-carbon negative electrode material in lithium ion battery
CN118373423A
Hard carbon negative electrode material and preparation method therefor, mixed negative electrode material, and secondary battery
WO2024108771A1
Cited By
High-capacity nitrogen-doped porous silicon-oxygen-carbon negative electrode material as well as preparation method and application thereof
CN120809769A
High-capacity nitrogen-doped porous silicon-oxygen-carbon anode materials, their preparation methods and applications
CN120809769B
Composite silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and battery
CN121769034A